Job challenge profile participant workbook. - McCauley, Cynthia D. (Center for Creative Leadership ;, 2015)
The Job Challenge Profile (JCP) Participant Workbook is used to support the the self-scoring Job Challenge Survey. The JCP Survey is a tool designed for managers and executives to help them understand and use their job assignments as opportunities to develop valuable skills. The Participant Workbook is a resource to be used by those taking the Survey.